Pre-Operative Intravitreal Bevacizumab (Avastin) Injection before Diabetic Vitrectomy - Saad A. Waheeb (Journal of King Abdulaziz University: Medical Sciences, 2023)
Evaluate the effect of intravitreal Avastin® prior to diabetic vitrectomy surgery and assess outcomes on OR time and inter-op block as major advantages. At King Faisal Specialist Hospital and King Abdulaziz University Hospital both in Jeddah, Saudi Arabia plus in UK tertiary care health facilities, 20 eyes underwent diabetic vitrectomy in June 2008 to June 2009; included and randomized to a standard vitrectomy (group 1/ control) or with preoperative Avastin® (group 2/ study). Avastin was injected 7-14 days preoperative for surgery; main outcomes were surgery feasibility and postoperative complications. Follow-up ranged between 6 and 12 months. A significant reduction of mean surgical time, bleeding frequency and diathermy were noted in group 2 compared to group 1. Gas or air was used in 80% of patients (group 2), while silicone oil 60% (group 1). Postoperative visual acuity improvement was highly significant in both groups. Primary anatomical attachment was achieved in 90.3% (group 2) and 86.6% (group 1). Rate of subsequent surgeries and persistent cataract were higher in group 1. Postoperative bleeding was reported in 26.6% in group 1 and none in group 2 (none related to Avastin® injection or progression of traction). Preoperative Avastin® successfully achieved the goal in diabetic vitrectomy surgery.